Impairment of kidney function and kidney cancer: A bidirectional Mendelian randomization study. (7th September 2022) - Lin, Yifei; Yang, Yong; Fu, Tingting; Lin, Ling; Zhang, Xingming; Guo, Qiong; Chen, Zhenglong; Liao, Banghua; Huang, Jin
Abstract: Background: Many observational epidemiology studies discovered that kidney cancer and impaired kidney function have a bidirectional relationship. However, it remains unclear whether these two kinds of traits are causally linked. In this study, we aimed to investigate the bidirectional causal relation between kidney cancer and kidney function biomarkers (creatinine‐based estimated glomerular filtration rate (eGFRcrea), cystatin C‐based estimated glomerular filtration rate (eGFRcys), blood urea nitrogen (BUN), serum urate, and urinary albumin‐to‐creatinine ratio (UACR)). Methods: For both directions, single‐nucleotide polymorphisms (SNPs), as genetic instruments, for the five kidney function traits were selected from up to 1, 004, 040 individuals, and SNPs for kidney cancer were from 408, 786 participants(1338 cases). In the main analysis, we applied two state‐of‐the‐art MR methods, namely, contamination mixture and Robust Adjusted Profile Score to downweight the effect of weak instrument bias, pleiotropy, and extreme outliers. We additionally conducted traditional MR analyses as sensitivity analyses. Summary‐level data of European ancestry were extracted from UK Biobank, Chronic Kidney Disease Genetics Consortium, and Kaiser Permanente. Results: Based on 99 SNPs, we found that the eGFRcrea had a significant negative causal effect on the risk of kidney cancer (OR = 0.007, 95% CI:2.6 × 10 −4 –0.569, p = 0.041). After adjusting for body composition or diabetes, urate had a significant negative causal effect on kidney cancer (OR <1, p < 0.05). For UACR, it showed a strong causal effect on kidney cancer, after adjusting for body composition (OR = 14.503, 95% CI: 2.546–96.001, p = 0.032). Due to lacking significant signals and effect power for the reverse MR, further investigations are warranted. Conclusions: Our study suggested a potential causal effect of damaged kidney function on kidney cancer. EGFRcrea and UACR might be causally associated with kidney cancer, especially when patients were comorbid with obesity or diabetes. We called for larger sample‐size studies to further unravel the underlying causal relationship and the exact mechanism. Abstract : It remains unclear whether kidney cancer and impaired kidney function are causally linked. Using various Mendelian randomization methods, we found eGFRcrea and UACR might be important predictors of the risk of kidney cancer, while eGFRcys might be a key biomarker to identify whether kidney function was harmed, regardless of the partial nephrectomy performed.